Veneer-based laminated flame-retardant tough material as well as preparation method and application thereof

By modifying the combination of inorganic flame retardant particles and ammonium polyphosphate on wood, a high-strength gel structure is formed, which solves the problem of difficult to take into account both the flame retardant performance and mechanical strength in traditional flame retardant treatment, and achieves high flame retardant of the material and mechanical strength, and reduce environmental pollution risks.

CN119217489APending Publication Date: 2024-12-31ZHEJIANG FORESTRY UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411752402.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

When traditional flame retardants treat wood, flame retardant performance and mechanical strength are difficult to take into account, and there are problems such as environmental pollution and complex equipment.

Method used

By modifying and crosslinking the inorganic flame retardant particles containing hydroxyl groups with ammonium polyphosphate in sodium alginate solution, a high-strength gel structure is formed, combined with calcium ion polymerization, a high-strength gel structure is prepared with excellent flame retardant properties and high mechanical strength. Veneer base layered flame retardant and tough material.

Benefits of technology

It realizes the high flame retardancy, mechanical strength and environmental protection of the materials, and is suitable for interior materials of buildings, furniture and transportation tools, extends service life and reduces the risk of environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119217489A_ABST
    Figure CN119217489A_ABST
Patent Text Reader

Abstract

The invention discloses a veneer-based laminated flame-retardant tough material and a preparation method and application thereof.The preparation method comprises the following steps that hydroxyl-containing inorganic flame-retardant particles are immersed in an aromatic dicarboxylic acid solution to obtain modified flame-retardant particles, the modified flame-retardant particles and ammonium polyphosphate are added into a sodium alginate solution to be mixed to be uniform, and the veneer-based laminated flame-retardant tough material is obtained. Pre-polymerization liquid is obtained; and S2, immersing delignified balsa wood veneers into the pre-polymerization liquid obtained in the step S1, stacking the balsa wood veneers layer by layer, immersing the balsa wood veneers into a calcium ion solution, and drying the balsa wood veneers after polymerization to form the veneer-based laminated flame-retardant tough material. According to the invention, ammonium polyphosphate is used as a flame-retardant material, delignification treatment is carried out on cork wood, carboxylic acid modification is carried out on hydroxyl-containing inorganic flame-retardant particles, and polymerization is carried out on sodium alginate and calcium ions, so that the material with excellent flame-retardant property and high mechanical strength is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a flame-retardant high-strength plate material, in particular to a single-board-based laminated flame-retardant strong-tough material and a preparation method and application thereof. Background Art

[0002] Wood is widely used in construction, transportation, furniture and interior decoration, but its flammability can easily lead to fire hazards, causing casualties and property losses. Using appropriate flame retardants to treat wood is of great significance to further broaden the scope of wood use, safeguard people’s property safety, and ensure stable growth of the national economy.

[0003] In order to improve the flame retardant properties of wood materials, they usually need to be flame retardant treated. Coating the surface of the wood and its products after final processing with flame retardants or flame retardant coatings such as polybrominated biphenyls, red phosphorus, antimony trioxide, etc. is an effective flame retardant treatment method, or sticking non-combustible substances on the surface of the wood can also achieve the purpose of heat insulation and oxygen isolation through the protective layer. The advantage of surface coating is that it has little effect on the physical and mechanical properties of wood, is easy to operate, and has simple equipment, but the disadvantage is that once the protective layer is damaged, the flame retardant properties disappear immediately. In addition, flame retardants such as polybrominated biphenyls, red phosphorus, antimony trioxide, etc. also have environmental pollution and may affect the mechanical properties of the material. Summary of the invention

[0004] In view of the problem that the wood treated with traditional flame retardants has poor flame retardancy and mechanical strength, the present invention provides a single-board-based laminated flame retardant and tough material and a preparation method and application thereof, which has both flame retardancy and high mechanical strength.

[0005] In order to achieve the above object, the present invention provides a method for preparing a single-board-based laminated flame-retardant and tough material, which comprises the following steps: S1, immersing hydroxyl-containing inorganic flame retardant particles in an aromatic dicarboxylic acid solution to obtain modified flame retardant particles, adding the modified flame retardant particles and ammonium polyphosphate into a sodium alginate solution and mixing them evenly to obtain a prepolymer solution; S2, immersing the delignified balsa wood veneer into the prepolymer solution obtained in step S1, stacking them layer by layer and immersing them in a calcium ion solution, and drying them after polymerization to form a veneer-based laminated flame-retardant and tough material.

[0006] The present invention uses ammonium polyphosphate as a flame retardant material, performs delignification treatment on balsa wood, modifies inorganic flame retardant particles containing hydroxyl groups, and polymerizes sodium alginate and calcium ions to prepare a material with excellent flame retardant properties and high mechanical strength. During the preparation process, by regulating the content of ammonium polyphosphate, the functional groups such as amino, hydroxyl, and carboxyl groups in the regulation system can form hydrogen bonds with tissues to optimize the flame retardant properties and mechanical strength of the material. The acidic gas released by ammonium polyphosphate at high temperature is combined with the barrier effect of inorganic flame retardant particles containing hydroxyl groups, which helps to improve the flame retardant properties of the composite material. By adding a specific proportion of sodium alginate and calcium ions for cross-linking, a high-strength gel structure is formed after drying. The gel can evenly disperse the inorganic flame retardant particles containing hydroxyl groups and particles such as ammonium polyphosphate in a matrix to avoid particle aggregation or uneven dispersion. The gel has a three-dimensional cross-linked structure, which can provide more support, so that the composite material is not easy to break when stretched or stressed, and the structural stability and service life of the material are improved.

[0007] The preparation method of the present invention has the advantages of being simple and sustainable. The flame-retardant and tough material obtained has high flame retardancy, high mechanical strength, environmental protection, and safety, and is suitable for a variety of application scenarios.

[0008] Specifically, in step S1, the hydroxyl-containing inorganic flame retardant particles are selected from one or more of kaolin, bentonite, and bauxite; this type of flame retardant particles contains hydroxyl groups, which react with the carboxyl groups of carboxylic acids to form stable chemical bonds. This type of substance also has negatively charged groups. Since the Si-O and Al-O on the surface carry a certain negative charge, they react with the hydrogen ions in the carboxylic acids to enhance the interfacial adhesion between them and other components (such as sodium alginate, ammonium polyphosphate, etc.). Bentonite has good adsorption and thermal stability, and can expand at high temperatures to form a heat-insulating layer, thereby playing a flame retardant role. Its performance at high temperatures is similar to that of kaolin, and it has good cost-effectiveness. Bauxite contains a high content of aluminum oxide (Al2O3), which has a high thermal stability. It can not only improve the thermal stability of the material, but also form an aluminum oxide layer during combustion, further isolating the fire source and enhancing the flame retardant effect.

[0009] The aromatic dicarboxylic acid is selected from one or more of phthalic acid, terephthalic acid and isophthalic acid.

[0010] Specifically, in step S1, the mass ratio of the hydroxyl-containing inorganic flame retardant particles to the aromatic dicarboxylic acid is 1:(1-1.2), and the immersion time is 20-24 hours.

[0011] Aromatic dicarboxylic acids have carboxylic acid groups (-COOH). The oxygen atoms in the carboxylate group form hydrogen bonds with more covalent components with the hydrogen atoms on the surface of the hydroxyl-containing inorganic flame retardant particles, thereby enhancing the chemical affinity between the two. The carboxylate ions can be stably adsorbed on the surface of the hydroxyl-containing inorganic flame retardant particles, and then through hydrogen bonds and electrostatic forces, the interfacial adhesion between the hydroxyl-containing inorganic flame retardant particles and other components (such as sodium alginate, ammonium polyphosphate, etc.) can be enhanced.

[0012] By modifying the hydroxyl-containing inorganic flame retardant particles, the role of the aromatic dicarboxylic acid is to add an organic modification layer, which can improve its thermal stability and chemical stability at high temperatures to a certain extent, indirectly improve the flame retardant properties of the material, form a strong interface bonding force with sodium alginate and ammonium polyphosphate, and enhance the overall strength and toughness of the composite material.

[0013] Preferably, the concentration of the aromatic dicarboxylic acid in the aromatic dicarboxylic acid solution is 10-20 g / 150 mL ethanol.

[0014] Preferably, in step S1, the mass ratio of the modified flame retardant particles, ammonium polyphosphate and sodium alginate is (1-1.5): (1-1.5): (1.5-2).

[0015] Specifically, in step S2, the preparation method of the delignified balsa wood veneer is: soak the balsa wood veneer in a mixed solution of sodium hydroxide and sodium sulfite for 3 to 4 hours, and then soak it in a mixed solution of sodium chlorite and acetic acid at 50 to 60° C. for 2 to 3 hours.

[0016] Delignification of balsa wood can expand the internal voids of balsa wood, which is beneficial for the gel prepolymer to penetrate and fill the voids.

[0017] Preferably, in the mixed solution of sodium hydroxide and sodium sulfite, the concentration of sodium hydroxide is 10-15 wt%, and the concentration of sodium sulfite is 5-6 wt%; in the mixed solution of sodium chlorite and acetic acid, the concentration of sodium chlorite is 1-1.5 wt%, and the concentration of acetic acid is 0.01-0.02 wt%.

[0018] Specifically, in step S2, the stacked balsa wood is immersed in the prepolymer solution for 1 to 2 hours.

[0019] Preferably, in step S2, the calcium ion solution is a calcium chloride solution, and the calcium chloride concentration is 0.5 wt%.

[0020] The second aspect of the present invention provides a single-board-based laminated flame-retardant and tough material obtained by the above-mentioned preparation method.

[0021] The third aspect of the present invention provides the use of the above-mentioned single-board-based laminated flame-retardant and tough material in the preparation of building materials, furniture materials and vehicle interior materials.

[0022] Through the above technical solution, the present invention achieves the following beneficial effects: 1. The present invention uses ammonium polyphosphate as a flame retardant material, performs delignification treatment on balsa wood, performs carboxylic acid modification on hydroxyl-containing inorganic flame retardant particles, and polymerizes sodium alginate and calcium ions to prepare a material with excellent flame retardant properties and high mechanical strength. During the preparation process, by regulating the content of ammonium polyphosphate, the amino, hydroxyl, carboxyl and other functional groups in the system are regulated. These functional groups can form hydrogen bonds with tissues to optimize the flame retardant properties and mechanical strength of the material. By adding a specific proportion of sodium alginate and calcium ions for cross-linking, a high-strength structure is formed after drying, thereby improving the structural stability and service life of the material.

[0023] 2. The present invention can expand the internal voids of balsa wood by delignifying the balsa wood, which is beneficial for the gel prepolymer to penetrate and fill the voids, thereby improving the mechanical strength and flame retardant properties of the material.

[0024] 3. The present invention modifies the hydroxyl-containing inorganic flame retardant particles and introduces carboxyl groups, which can greatly improve the dispersibility of the hydroxyl-containing inorganic flame retardant particles, strengthen the hydrogen bonding effect between the hydroxyl-containing inorganic flame retardant particles and sodium alginate, and improve the mechanical strength.

[0025] 4. The flame-retardant high-strength board material prepared by the present invention is suitable for the fields of building materials, furniture materials and transportation interior materials, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a physical picture of the material prepared in Example 1 of the present invention and a scanning electron microscope (SEM) image of the interface bonding of the gel wood board; Figure 2 The tensile strength test results of the materials prepared in the embodiments and comparative examples are as follows; Figure 3 These are the flame retardant performance test results of the materials prepared in the examples and comparative examples. DETAILED DESCRIPTION

[0027] The specific implementation of the present invention is described in detail below in conjunction with the examples. It should be understood that the specific implementation described herein is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0028] Example 1 The preparation method of the single-board-based laminated flame-retardant and tough material comprises the following steps: S1. Soak the balsa wood in a 10 wt% sodium hydroxide and 5.04 wt% sodium sulfite solution for 3 hours to remove part of the lignin and other impurities and enhance its bonding performance with flame retardant materials. After the treatment, take out the balsa wood and wash it repeatedly with deionized water until it is neutral to completely remove the alkaline substances and solution residues. Then place the washed balsa wood in a 1wt% sodium chlorite and 0.02 wt% acetic acid solution and react at 60°C for 3 hours to further remove the lignin component in the wood and obtain delignified balsa wood; S2. Soak 10g of kaolin in an ethanol solution with a phthalic acid concentration of 10 g / 150 mL for 24 hours for surface modification to improve its ability to bind to organic materials. After the soaking treatment, take out the kaolin and wash it repeatedly with deionized water until there is no excess organic solution remaining on its surface. The washed kaolin is dried to obtain modified kaolin. Then the modified kaolin, ammonium polyphosphate and sodium alginate are sampled in proportions of 2 g / 100mL, 2 g / 100 mL, and 3 g / 100 mL, respectively, placed in a container and added with an appropriate amount of deionized water, and stirred continuously for 12 hours under a stirrer until a uniform prepolymer solution is formed.

[0029] S3. Completely immerse the delignified balsa wood obtained in step S1 into the prepolymer solution obtained in step S2, and immerse it in a vacuum environment for 1 hour to ensure that the prepolymer solution fully penetrates into the balsa wood. Then stack the treated balsa wood boards layer by layer and immerse them in a 0.5 wt% calcium chloride solution to perform a cross-linking polymerization reaction to improve the structural stability and strength of the material. This step helps to form a uniform and stable composite material structure, giving it better flame retardant and mechanical properties. Finally, the impregnated and cross-linked wood is naturally air-dried at room temperature to completely remove moisture and obtain the final flame retardant high-strength board material. Figure 1 The actual picture of the flame-retardant high-strength board material and the scanning electron microscope (SEM) image of the interface bonding of the gel wood board are displayed, showing the uniformity of the internal structure of the material and the close bonding of the interface.

[0030] Example 2 S1. Soak the balsa wood in a 15 wt% sodium hydroxide and 6 wt% sodium sulfite solution for 2 hours to remove part of the lignin and other impurities and enhance its bonding performance with flame retardant materials. After the treatment, take out the balsa wood and wash it repeatedly with deionized water until it is neutral to completely remove the alkaline substances and solution residues. Then place the washed balsa wood in a 1.5wt% sodium chlorite and 0.01 wt% acetic acid solution and react at 50°C for 3 hours to further remove the lignin component in the wood and obtain delignified balsa wood; S2. Soak 10g of kaolin in an ethanol solution with a phthalic acid concentration of 12 g / 150 mL for 20 hours for surface modification to improve its ability to bind to organic materials. After the soaking treatment, take out the kaolin and wash it repeatedly with deionized water until there is no excess organic solution remaining on its surface. The washed kaolin is dried to obtain modified kaolin. Then the modified kaolin, ammonium polyphosphate and sodium alginate are sampled in proportions of 3 g / 100 mL, 2 g / 100 mL, and 4 g / 100 mL, respectively, placed in a container and added with an appropriate amount of deionized water, and stirred continuously for 12 hours under a stirrer until a uniform prepolymer solution is formed.

[0031] S3. Completely immerse the delignified balsa wood obtained in step S1 into the prepolymer solution obtained in step S2, and immerse it in a vacuum environment for 2 hours to ensure that the prepolymer solution fully penetrates into the balsa wood. Then stack the treated balsa wood boards layer by layer and immerse them in a 1 wt% calcium chloride solution to perform a cross-linking polymerization reaction to improve the structural stability and strength of the material. This step helps to form a uniform and stable composite material structure, giving it better flame retardant and mechanical properties. Finally, the impregnated and cross-linked wood is naturally air-dried at room temperature to completely remove moisture and obtain the final flame retardant high-strength board material.

[0032] Example 3 S1. Soak the balsa wood in a 12 wt% sodium hydroxide and 5.5 wt% sodium sulfite solution for 3 hours to remove part of the lignin and other impurities and enhance its bonding performance with flame retardant materials. After the treatment, take out the balsa wood and wash it repeatedly with deionized water until it is neutral to completely remove the alkaline substances and solution residues. Then place the washed balsa wood in a 1.2 wt% sodium chlorite and 0.02 wt% acetic acid solution and react at 60°C for 2 hours to further remove the lignin component in the wood and obtain delignified balsa wood; S2. Soak 10g of bentonite and 10g of bauxite in an ethanol solution with a terephthalic acid concentration of 20 g / 150 mL for 24 hours for surface modification to improve its ability to bind to organic materials. After the soaking treatment, take out the bentonite and bauxite, and wash them repeatedly with deionized water until there is no excess organic solution remaining on the surface. The washed bentonite and bauxite are dried to obtain modified bentonite and bauxite. Then the modified bentonite and bauxite are sampled with ammonium polyphosphate and sodium alginate in proportions of 2 g / 100 mL, 3 g / 100 mL, and 3 g / 100 mL, respectively, placed in a container and added with an appropriate amount of deionized water, and stirred continuously for 24 hours under a stirrer until a uniform prepolymer solution is formed.

[0033] S3. Completely immerse the delignified balsa wood obtained in step S1 into the prepolymer solution obtained in step S2, and immerse it in a vacuum environment for 2 hours to ensure that the prepolymer solution fully penetrates into the balsa wood. Then stack the treated balsa wood boards layer by layer and immerse them in a 0.8 wt% calcium chloride solution to perform a cross-linking polymerization reaction to improve the structural stability and strength of the material. This step helps to form a uniform and stable composite material structure, giving it better flame retardant and mechanical properties. Finally, the impregnated and cross-linked wood is naturally air-dried at room temperature to completely remove moisture to obtain the final flame retardant high-strength board material.

[0034] Example 4 S1. Soak the balsa wood in a 10 wt% sodium hydroxide and 5.2 wt% sodium sulfite solution for 3 hours to remove part of the lignin and other impurities and enhance its bonding performance with flame retardant materials. After the treatment, take out the balsa wood and wash it repeatedly with deionized water until it is neutral to completely remove alkaline substances and solution residues. Then place the washed balsa wood in a 1wt% sodium chlorite and 0.02 wt% acetic acid solution and react at 60°C for 3 hours to further remove the lignin component in the wood and obtain delignified balsa wood; S2. Soak 15g of bauxite in an ethanol solution with an isophthalic acid concentration of 15 g / 150 mL for 24 hours for surface modification to improve its ability to bind to organic materials. After the soaking treatment, take out the bauxite and wash it repeatedly with deionized water until there is no excess organic solution remaining on its surface. The washed bauxite is dried to obtain modified bauxite. Then the modified bauxite is sampled with ammonium polyphosphate and sodium alginate in proportions of 3 g / 100 mL, 3 g / 100 mL, and 3 g / 100 mL, respectively, placed in a container and added with an appropriate amount of deionized water, and stirred continuously for 12 hours under a stirrer until a uniform prepolymer solution is formed.

[0035] S3. Completely immerse the delignified balsa wood obtained in step S1 into the prepolymer solution obtained in step S2, and immerse it in a vacuum environment at 10°C for 1.5 hours to ensure that the prepolymer solution fully penetrates into the balsa wood. Then stack the treated balsa wood boards layer by layer and immerse them in a 0.5 wt% calcium chloride solution to perform a cross-linking polymerization reaction to improve the structural stability and strength of the material. This step helps to form a uniform and stable composite material structure, giving it better flame retardant and mechanical properties. Finally, the impregnated and cross-linked wood is naturally air-dried at room temperature to completely remove moisture to obtain the final flame retardant high-strength board material.

[0036] Comparative Example 1 Other conditions were the same as in Example 1, except that ammonium polyphosphate was omitted.

[0037] Comparative Example 2 Other conditions were the same as in Example 1, except that the concentration of the calcium chloride solution was 0.2 wt %.

[0038] Comparative Example 3 Other conditions were the same as those in Example 1, except that the kaolin was not modified with phthalic acid.

[0039] Performance Testing The mechanical properties and flame retardant properties of the materials obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were tested respectively.

[0040] Mechanical properties: The mechanical properties of the material are measured using a microcomputer mechanical testing machine. Based on the measurement results of the tensile test, the tensile strength of the material is calculated. The specific method is: place the prepared material between the furniture and use the microcomputer mechanical testing machine to measure its tensile strength. The specific test results are as follows: Figure 2 As shown. Figure 2 It can be seen that the maximum tensile strength of the flame retardant and tough materials prepared by Examples 1 to 4 is 980±100 MPa, while the maximum tensile strength of the materials prepared by Comparative Examples 1 to 3 is only 480±162 MPa.

[0041] Flame retardant performance: The flame retardant performance of the material is tested using a cone calorimeter. The specific method is: fix the prepared material sample on the test frame, test it according to ISO 5660 standard, and record its ignition time, combustion heat release rate, total combustion heat release and other parameters. The specific test results are as follows: Figure 3 As shown. Figure 3 It can be seen that the flame retardant and tough materials prepared by Examples 1 to 4 exhibit a longer ignition time (average value of 115±5 seconds), a lower heat release rate and a total combustion heat release (average of 8.7±0.7 KJ / g); while the materials prepared by Comparative Examples 1 to 3 have a shorter ignition time (average value of 40±7 seconds), and a significantly higher heat release rate and a total combustion heat release (average of 13.8±0.7 KJ / g), exhibiting poor flame retardant properties.

[0042] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0043] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0044] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing a single-board-based laminated flame-retardant and tough material, characterized in that: The steps include: S1, immersing hydroxyl-containing inorganic flame retardant particles in an aromatic dicarboxylic acid solution to obtain modified flame retardant particles, adding the modified flame retardant particles and ammonium polyphosphate into a sodium alginate solution and mixing them evenly to obtain a prepolymer solution; S2, immersing the delignified balsa wood veneer into the prepolymer solution obtained in step S1, stacking them layer by layer and immersing them in a calcium ion solution, and drying them after polymerization to form a veneer-based laminated flame-retardant and tough material.

2. The preparation method according to claim 1, characterized in that: In step S1, the hydroxyl-containing inorganic flame retardant particles are selected from one or more of kaolin, bentonite, and bauxite; and the aromatic dicarboxylic acid is selected from one or more of phthalic acid, terephthalic acid, and isophthalic acid.

3. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the hydroxyl-containing inorganic flame retardant particles to the aromatic dicarboxylic acid is 1:(1-1.2), and the immersion time is 20-24 hours.

4. The preparation method according to claim 3, characterized in that The concentration of the aromatic dicarboxylic acid in the aromatic dicarboxylic acid solution is 10-20 g / 150 mL ethanol.

5. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the modified flame retardant particles, ammonium polyphosphate and sodium alginate is (1-1.5): (1-1.5): (1.5-2).

6. The preparation method according to claim 1, characterized in that: In step S2, the preparation method of the delignified balsa wood veneer is: soak the balsa wood veneer in a mixed solution of sodium hydroxide and sodium sulfite for 3 to 4 hours, and then soak it in a mixed solution of sodium chlorite and acetic acid at 50 to 60° C. for 2 to 3 hours.

7. The preparation method according to claim 6, characterized in that In the mixed solution of sodium hydroxide and sodium sulfite, the concentration of sodium hydroxide is 10-15 wt %, and the concentration of sodium sulfite is 5-6 wt %; in the mixed solution of sodium chlorite and acetic acid, the concentration of sodium chlorite is 1-1.5 wt %, and the concentration of acetic acid is 0.01-0.02 wt %.

8. The preparation method according to claim 1, characterized in that: In step S2, the stacked balsa wood is immersed in the prepolymer solution for 1 to 2 hours.

9. The single-board-based laminated flame-retardant and tough material obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the single-board-based laminated flame-retardant and tough material according to claim 9 in the preparation of building materials, furniture materials and vehicle interior materials.